Effect of Docetaxel on Matrix Metalloproteinase 1 Expression in Freund’s Adjuvant Induced Arthritis - Alghulami, Omar; Ghaith A. Jasim; Suzan Yousif Jasim (Iraqi Journal of Pharmaceutical Sciences, 2024)
Rheumatoid arthritis is an autoimmune disorder that affects the synovial joints. It lead to inflammatory changes occur in synovial tissue, cartilage, bone, and, less frequently, extra-articular structures. Docetaxel, is an anti-neoplastic drug. Methotrexate is a treatment for early-stage rheumatoid arthritis but have 30% failure in treatment within the first year due to resistance or side effects. Matrix metalloproteinase 1 is the proteinase primarily in charge of the irreversible degradation of cartilage, bone, and tendons in the joints, which are induced by cytokines. This study aims to evaluate the effects of docetaxel and methotrexate on Matrix metalloproteinase 1 in the structure of the induced arthritis joints. Methods: To induce the disease, complete Freund’s adjuvant is injected subcutaneously into rats. From the 40 male Wister rats, five groups of eight were formed. The control group is composed of non-diseased rats. The second group is induced by complete Freund’s adjuvant and 0.5 ml of normal saline was administered intraperitoneally to both the control and induction groups. After being induced by complete Freund’s adjuvant, the third group is administered 1 mg/kg/ on alternate day of Docetaxel based on a preliminary experiment. The fourth group is induced and given 1 mg/kg/week of Methotrexate intraperitoneally. The fifth group receives a half dose of Methotrexate and Docetaxel simultaneously. Serum level of Anti Cyclical citrullinated Peptide Antibody, tissue homogenate level of tumor necrosis factor-alpha, knee joint circumference and Immunohistochemical of Matrix metalloproteinase 1 measurements were applied. Results: Significant decreased in the Serum level of Anti-Cyclic citrullinated Peptide Antibody, tissue homogenate level of tumor necrosis factor-alpha & Knee joint circumference in the Docetaxel group. significant lowering in the expression of Matrix metalloproteinase 1 immunoreactivities in Docetaxel and Methotrexate groups with almost absent spots of positive reaction with the matrix of synovial tissue, hyaline cartilage & articular surface. Conclusion: This study showed that Docetaxel may have anti-arthritic effect through their significant lowering expression of Matrix metalloproteinase 1 immunoreactivities.